Can Synovial Pathobiology Integrate with Current Clinical and Imaging Prediction Models to Achieve Personalized Health Care in Rheumatoid Arthritis? - Humby, Frances Claire; Al Balushi, Farida; Lliso, Gloria; Cauli, Alberto; Pitzalis, Costantino (Frontiers in Medicine, 2017)
Although great progress has been made in the past decade towards understanding the pathogenesis of rheumatoid arthritis clinicians remain some distance from a goal of personalised healthcare. The capacity to diagnose RA early, predict prognosis and moreover predict response to biologic therapies has been a research focus for many years. How currently available clinical prediction models can facilitate such goals is reviewed in this article. In addition the role of current imaging techniques in this regard is also discussed. Finally the authors review the current literature regarding synovial biomarkers and consider whether integration of synovial pathobiology into clinical prediction algorithms may enhance their predictive value.